Who bears the costs of climate change? Evidence from Tunisia - Wiebelt, Manfred; Al-Riffai, Perrihan; Breisinger, Clemens; Robertson, Richard D. (Project MUSE, 2015)
In order to estimate the economic costs of climate change for Tunisia, this paper uses a combination of biophysical and economic models. In addition, the paper draws on the literature to complement the quantitative analysis with policy recommendations on how to adapt to the changing climate. The results bear out the expectation that climate change has a negative but weak overall effect on the Tunisian economy. Decomposing the global and local effects shows that global climate change may benefit the agricultural sector since higher world market prices for agricultural commodities are likely to stimulate export expansion and import substitution. Locally felt climate change, however, is likely to hurt the agricultural sector as lower yields reduce factor productivities and lead to lower incomes and higher food prices. The combined local and global effects are projected to be mostly negative and the costs will have to be carried mainly by urban and richer households. From a policy perspective, the results suggest that Tunisia should try to maximize the benefits from rising global agricultural prices and to minimize (or reverse) declining crop yields at home.